Survey Approaches In Green Supply Chain Management Research: An Analysis - Wan Mahmood, Wan Hasrulnizzam; Ab Rahman, Mohd Nizam; Md Deros, Baba (2010)
Survey is an approved method that has been used by researchers for many years ago. The effectiveness of the method cannot be denied and until today, it is still the best method to identify a population perspective on the particular thing or anything that related to the purpose of a study. The aim of this paper is to examine the extent of the survey approaches in green supply chain management (GSCM) research. The findings show that GSCM survey-based research is mainly conducted in Asian countries regions which focused on the GSCM practice and performance. Postal survey is the most preferred in data collection as well as survey are also distributed in workshops. Analysis methods such structural equation modeling (SEM), conformity factor analysis (CFA), non-parametric test, correlation test, regression analysis, and ANOVA were selected to test the researches hypotheses while SPSS and AMOS are the favourite software that used for the analysis.